Internal migration in Spain: A complementary approach - Adolfo Maza (Economies, 2020)
This study examines the determinants of internal migration of working-age population among provinces in Spain in the aftermath of the economic crisis. It pays special attention to two features of migration that have not been sufficiently studied so far: (a) Distance, namely the differences between the determinants that are behind short-distance and long-distance movements; (b) Age, that is to say, whether young and adult migrants hold different motivations. To accomplish this aim, an extended model is used in which, apart from a variable capturing distance, both economic and non-economic (amenities) variables are included. Findings reveal that both economic factors (mainly unemployment and income) and amenities (measured by a climate condition variable) are more important for adult population and long-distance movements than for young population and movements between neighbouring provinces. Additional findings seem to convey the message that, as far as housing prices are concerned, they play a significant role when migration takes place between neighbouring provinces, but lose importance when all migrations are studied together. Moreover, the paper's results do not cast, as expected, any doubt on the importance of distance regardless of the type of migration or age of the migrant.
Keywords: R23; O15; C23; 330; internal migration; distance; age; migration model; Spanish provinces